Geometric Deformations of the Thoracic Aorta and Supra-Aortic Arch Branch Vessels Following Thoracic Endovascular Aortic Repair. (April 2018) - Ullery, Brant W.; Suh, Ga-Young; Hirotsu, Kelsey; Zhu, David; Lee, Jason T.; Dake, Michael D.; Fleischmann, Dominik; Cheng, Christopher P.
Objective: To utilize 3-D modeling techniques to better characterize geometric deformations of the supra-aortic arch branch vessels and descending thoracic aorta after thoracic endovascular aortic repair. Methods: Eighteen patients underwent endovascular repair of either type B aortic dissection (n = 10) or thoracic aortic aneurysm (n = 8). Computed tomography angiography was obtained pre- and postprocedure, and 3-D geometric models of the aorta and supra-aortic branch vessels were constructed. Branch angle of the supra-aortic branch vessels and curvature metrics of the ascending aorta, aortic arch, and stented thoracic aortic lumen were calculated both at pre- and postintervention. Results: The left common carotid artery branch angle was lower than the left subclavian artery angles preintervention ( P < .005) and lower than both the left subclavian and brachiocephalic branch angles postintervention ( P < .05). From pre- to postoperative, no significant change in branch angle was found in any of the great vessels. Maximum curvature change of the stented lumen from pre- to postprocedure was greater than those of the ascending aorta and aortic arch ( P < .05). Conclusion: Thoracic endovascular aortic repair results in relative straightening of the stented aortic region and also accentuates the native curvature of the ascending aorta when the endograft has a more proximal landing zone. Supra-aortic branch vessel angulation remains relatively static when proximal landing zones are distal to the left common carotid artery.